CAPAIAN MATURITAS SMART GOVERNANCE DALAM PELAYANAN PUBLIK DI KOTA MAKASSAR - a hidayat kaisar pais; Djunaedi, Achmad (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2025)
The Gerakan Menuju 100 Smart City (Movement Toward 100 Smart Cities) is an initiative launched in 2017 by the Ministry of Communication and Informatics of the Republic of Indonesia to accelerate the implementation of the smart city concept in one hundred cities and regencies across the country. A smart city is an urban management concept that utilizes digital technology to improve the quality of public services. This concept promotes a more efficient and responsive government, which is realized through smart governance. This study selects Makassar City as a case study to measure the maturity level of smart governance, based on the city’s participation in the national smart city movement. The objective of this research is to evaluate the implementation of the smart city program, particularly in the aspect of smart governance. The maturity assessment in this study applies a mixed-method approach to provide findings that accurately reflect current conditions, emphasizing the maturity aspects of smart governance related to public service delivery. Overall, the maturity achievement of smart governance in public services in Makassar City is at the integrated level, indicating that service systems are well-integrated but still have room for improvement—especially in enhancing online public services and expanding sensor coverage within infrastructure components—to elevate Makassar’s maturity level to the next stage, namely smart.